Pengaruh Gaya Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Arungkeke Kabupaten Jeneponto - Rusli Rusli; Maryadi Maryadi; Saripuddin Saripuddin; Abdul Rahman Jannang (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to analyze 1) partially the influence of leadership style, motivation and work discipline on employee performance at the Arungkeke District Office, Jeneponto Regency. 2) The simultaneous influence of Leadership Style, Motivation and Work Discipline on the Performance of Arungkeke District Office Employees, Jeneponto Regency. 3) The most dominant variable has an effect on the performance of Arungkeke District Office Employees, Jeneponto Regency. This research was conducted on employees of the Arungkeke District Office, Jeneponto Regency. Determination of the sample using the saturation technique by taking the entire existing population, as many as 32 employees of the Arungkeke District Office, Jeneponto Regency. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results of the study concluded that: partially Leadership Style, Motivation and Work Discipline had a positive and significant effect on the Performance of Arungkeke District Office Employees, Jeneponto Regency. This means that Leadership Style, Motivation and Work Discipline are able to improve the Performance of Arungkeke District Office Employees, Jeneponto Regency. Simultaneously Leadership Style, Motivation and Work Discipline have a positive and significant effect on the Performance of Arungkeke District Office Employees, Jeneponto Regency. Partially, it shows that the leadership style variable has a dominant effect on the performance of the Arungkeke District Office Employees, Jeneponto Regency.